Inhibitory transcranial magnetic theta burst stimulation attenuates prefrontal cortex oxygenation. Issue 1 (14th October 2011) - Tupak, Sara V.; Dresler, Thomas; Badewien, Meike; Hahn, Tim; Ernst, Lena H.; Herrmann, Martin J.; Deckert, Jürgen; Ehlis, Ann‐Christine; Fallgatter, Andreas J.
Abstract Recent studies highlighted the great potential of newly established theta burst stimulation (TBS) protocols for non‐invasive human brain stimulation studies using transcranial magnetic stimulation (TMS). While intermittent TBS over the primary motor cortex was found to potentiate motor evoked potentials, continuous TBS led to profound attenuations. Although numerous studies investigated the impact of TBS on motor cortex function, yet, only few imaging studies focused on its effects in other brain areas. Particularly for the prefrontal cortex, it is unclear whether TBS has similar effects compared to application over motor areas. In the current study continuous TBS was applied to either the left or right dorsolateral prefrontal cortex in a sample of healthy subjects. Changes in prefrontal oxygenation were measured during an emotional Stroop task by means of functional multi‐channel near‐infrared spectroscopy (fNIRS) before and after stimulation. Results showed bilaterally decreased prefrontal oxygenation following inhibitory stimulation of the left prefrontal cortex but no behavioral effect. No such alterations were observed following right‐hemispheric or sham stimulation. The results of the current study are in line with earlier findings and additionally demonstrate that also prefrontal oxygenation can be impaired by continuous TBS. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.